IMPORTANCE OF CLINICAL ASSESSMENT IN DIAGNOSIS OF ACUTE APPENDICITIS AND ITS ROLE IN DECREASING NEGATIVE APPENDICECTOMY RATE - Mehraj, Adnan; Naqvi, Muhammad Ali; Din, Hafeez Ud; Waqas, Waqas (Journal of Ayub Medical College Abbottabad, 2012)
Background: Appendicitis is a common diagnosis, but is by no means a simple one to establish. It is impractical to have a definitive preoperative diagnosis, which leads to an appreciable rate of negative appendicectomy as reported in world literature varying from 20-40% with its morbidity around 10%. This retrospective study investigated the value of clinical assessment and medical imaging (ultrasonography) for patients with suspected appendicitis. Negative appendicectomy rate and appendiceal perforation with or without medical imaging were used as end points for this investigation. Methods: This study reviewed all patients admitted in Sheikh Khalifa Bin Zaid Hospital with suspected acute appendicitis. The patient cohort was identified from the unit registry and review of medical records. The medical records were analysed, and the outcomes of patients were followed up. Results: Between June 2010 to June 2012, 375 patients' medical records were audited. These included 56.3% males and 43.7% females. The negative appendicitis rate was 7.2% and appendiceal perforation rate was 5.3%. Ultrasound was done in 103 (27.4%) patients in whom diagnosis of appendicitis was doubtful. Medical imaging had a 50% prediction rate for acute appendicitis, 40% false-negative rate, and 10% false-positive rate. Overall, the prediction rate for appendicitis by clinical assessment supplemented by laboratory tests and medical imaging at clinician's discretion was 92.8%. Conclusions: Despite studies advocating routine use of medical imaging for patients with suspected acute appendicitis, this study showed that the clinical evaluation is still paramount to the management of patients with suspected acute appendicitis before considering medical imaging. Keywords: Acute appendicitis, pain RIF, Clinical assessment, CT scan, Ultrasonography